ISIS, INDONESIAN MUSLIMS AND GLOBAL TERRORISM: A REFLECTION - Herdi Sahrasad; Al Chaidar Al Chaidar (Universitas Islam Negeri Alauddin Makassar, 2017)
The emergence of ISIL or ISIS, the Sunni militia, has shocked the Muslim World, including Indonesia. ISIS is the ultra jihadist for global terrorism. ISIS is also a translation from the Arabic, Ad-Daulah Islamiyah fi al-Iraq wa Ash-Sham. Some call it as Islamic State in Iraq and Syria (ISIS), which specifically has a different coverage area. The term includes the Sham or the Levant region between the Mediterranean Sea and the Euphrates River that the country coverage includes Jordan, Lebanon, Palestine, and Israel. The term Syria confined to the state of modern Syria that is currently in conflict. In this case, the involvement of hundreds Indonesians in the ISIS in the Middle East region is not new because previously, there is a precedent that some Indonesian citizens in the past had involvement in conflicts abroad when US President Jimmy Carter used the CIA to weaken the power of the Soviets in Afghanistan. In responding the ISIS networkers and followers in Indonesia, the Jakarta government and Muslim organizations like Nahdlatul Ulama (NU) dan Muhammadiyah have launched action and campaign for pluralism, peace, non-violence and civil Islam. The campaign by NU and Muhammadiyah for an open-minded and pluralistic Islam also comes in a time when Islam is at war with itself over central theological questions about how the faith defined in the modern era.